Menggagas Pembelajaran HOTS Pada Anak Usia Sekolah Dasar - Usmaedi Usmaedi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2017)
"The implementation of the Primary School Curriculum 2013 is done through partial learning towards an integrated learning, with a thematic approach-integrated from Class I to Class VI" (Permendikbud No. 65 and 67 in 2013). Integrated Thematic learning is implemented using the principles of integrated learning. The integration of the thematic order competency materials related to one another, so as to be mutually reinforcing, avoid overlapping and maintain alignment of learning (interdisciplinary) and contextual (transdisciplinary). Integrated thematic learning relevant to accommodate differences in qualitative learning environment, and is expected to inspire learners to acquire learning experience. Integrated thematic learning has a qualitatively different with other learning model, because it guides learners achieve higher levels of thinking to optimize multiple thinking skills, an innovative process for the development dimension of attitudes, skills and knowledge. However, the tendency has been teaching in elementary schools put more emphasis on (LOTS) Lower Order Thingking Skills are only able to answer factual questions which alternative is only one answer and the answer is usually something that can be found directly in the book or memorizing. Low-level thinking skills is the medium of higher thinking skills. That is why learning patterns that need to be initiated HOTS (Higher Order Thinking Skills). These skills need to be trained since elementary school age to make students familiar with the way of thinking that would be a high level of capital in the next education level. High-level thinking skills also make students able to convey ideas argumentative, logical, and self-confident, whether written, oral, and action..  Kata kunci : Pembelajaran, HOTS, keterampilan berfikir, Anak Usia Sekolah Dasar,